The Viral KSHV Chemokine vMIP-II Inhibits the Migration of Naive and Activated Human NK Cells by Antagonizing Two Distinct Chemokine Receptors - Yamin, Rachel (Public Library of Science, 2013)
Natural killer (NK) cells are innate immune cells able to rapidly kill virus-infected and tumor cells. Two NK cell populations are found in the blood; the majority (90%) expresses the CD16 receptor and also express the CD56 protein in intermediate levels (CD56(Dim) CD16(Pos)) while the remaining 10% are CD16 negative and express CD56 in high levels (CD56(Bright) CD16(Neg)). NK cells also reside in some tissues and traffic to various infected organs through the usage of different chemokines and chemokine receptors. Kaposi's sarcoma-associated herpesvirus (KSHV) is a human virus that has developed numerous sophisticated and versatile strategies to escape the attack of immune cells such as NK cells. Here, we investigate whether the KSHV derived cytokine (vIL-6) and chemokines (vMIP-I, vMIP-II, vMIP-III) affect NK cell activity. Using transwell migration assays, KSHV infected cells, as well as fusion and recombinant proteins, we show that out of the four cytokine/chemokines encoded by KSHV, vMIP-II is the only one that binds to the majority of NK cells, affecting their migration. We demonstrate that vMIP-II binds to two different receptors, CX3CR1 and CCR5, expressed by naïve CD56(Dim) CD16(Pos) NK cells and activated NK cells, respectively. Furthermore, we show that the binding of vMIP-II to CX3CR1 and CCR5 blocks the binding of the natural ligands of these receptors, Fractalkine (Fck) and RANTES, respectively. Finally, we show that vMIP-II inhibits the migration of naïve and activated NK cells towards Fck and RANTES. Thus, we present here a novel mechanism in which KSHV uses a unique protein that antagonizes the activity of two distinct chemokine receptors to inhibit the migration of naïve and activated NK cells.